Il gioco dei ruoli. Avanguardia e tradizione in Mein Herz e Der Malik di Else Lasker-Schüler (Altre Modernità, 2014)
Else Lansker-Schueler always tried to present her existence as a legend or a fairy tale.Her literary production is entirely based on the strong subjectivism of the german expressionism; also the Hebrew Mythology and its imagery is an important source of inspiration.The author,lying about her real life, constantly remains on the border between the Reality and the Poetry.The Lansker-Schuler's idea of a perfect identity between Life and Literature has brought as a consequence that her texts are read as a spontaneous poetization of her biography.Nonetheless, her literary production and letters are neither an ingenuous (auto)biography in line or in prose, nor a sure documetary source.In this essay I will explain that this attitude is nothing but the poetic construction of the Modernity central experience: the Subject, according to Frederick Nietzsche's Philosophy, is conscious that any social, religious, moral system is fictitious. Thinking so, only an autonomous poetic world can assure the (linguistic) surviving of the Ego.To demonstrate this hypothesis, I will focus on two prose texts which Else Lansker-Schuler composed,being inspired by her artistic and intellectual world (The berlin Bohème): Mein Herz (1912) and Der Malik (1919). In particular, I will deal with two elements, which are important in the representation of the Ego and in the construction of a language imagery: 1) The choice of the epistolary style; 2) the interaction between the roles played by the "Writing Ego" and by the surrounding characters.